Viability of producing lignocellulosic biomass in the Cape Winelands District Municipality for bioenergy generation - Von Doderer, Clemens Cornelius Christian (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Agricultural Economics)--University of Stellenbosch, 2009.